Internationalization paths of fruit export companies from emerging economies: Are they regionally or globally oriented?. Issue 2 (12th August 2019) - Losilla, Luis Vinicio; Engler, Alejandra; Otter, Verena
Abstract : Purpose: The purpose of this paper is to develop and apply a framework that examines the dynamics of internationalization strategies employed by export companies in the agricultural sector of emerging economies over time, with a focus on the locus of destination markets of the Chilean fruit sector. Thus, the objective is to identify conceptual and empirical deviations from existing research on export firms participating in non-agricultural sectors of industrialized countries. Design/methodology/approach: The matrix of multi-nationality developed by Aggarwal et al. (2011) is extended by incorporating the firm category of "host region" and the dimensions scale and time. This framework is utilized to classify 233 Chilean fresh fruit exporters according to their internationalization strategies based on a geographical distribution of their exports. A uni- and bivariate longitudinal analysis is conducted over a seven-year period (2009–2015) to explore the dynamics of this internationalization process. Findings: A significant number (12.75 percent) of firms classified as "host regional" are identified, and thus a clear difference in internationalization strategies when compared to non-agricultural sectors in industrialized countries. Simultaneously, similarities in these sectors can be found. Most firms are "transregionally" (65.12 percent) or "globally" oriented (16.06 percent), mainly following a linear internationalization path when considering the number of export markets. But there is also evidence of "born-global" firms, which mainly follow non-linear internationalization paths in more geographically and psychically distant markets. Research limitations/implications: The extended framework developed in this research can be applied to future studies, particularly in the case of economies where a significant proportion of firms are predominantly focusing their export strategies on one single international market. Since this study focuses on one national sector as a prime example, further studies on other countries and sectors may provide additional evidence of its generalizability. Practical implications: Based on the findings, concrete measures have been suggested to aid Chilean policy makers in implementing evidence-based economic policies, as well as Chilean public trade organizations and private export associations in the fruit sector, in relation to services such as training, strategy consulting and trade network development that they provide to export firms. Originality/value: The study contributes to the existing literature by introducing the firm category "host regional" into the matrix of multi-nationality, and empirically verifies its existence among agricultural export firms in emerging economies. Furthermore, it also shows that even when it might result counterintuitive, firms from the agricultural sector share similarities in internationalization strategies with firms from industrial sectors.